When Finnish and Karelian person systems come together: Comparing open person constructions in Border Karelian dialects - Uusitupa, Milla (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2021)
Abstract. This article is a contribution to the recent discussion on open reference and especially on open second-person singular usage in Finnish and other European languages. The article focuses on four referentially open person constructions – namely the zero construction, the necessive construction, the second-person singular construction, and the imperative construction – and their interplay and variation in spoken discourse in Border Karelian dialects. The aim of this article is three-fold. First and foremost, it argues that the aforementioned open person constructions are fundamentally four separate types. Second, it aims to expand the on-going discussion on open reference in Finnish by introducing the person system of its closely related but highly endangered cognate language, Karelian. Third, it raises the following question: In a wider Finnic context, is the zero construction, above all, a Finnish way of leaving the reference open and unspecified? Kokkuvõte. Milla Uusitupa: Kui soome ja karjala isikusüsteemid kohtuvad: avatud isikukonstruktsioonide võrdlus piiriala karjala murretes. Artikkel on täiendus hiljutisele diskussioonile avatud viitesuhtest ja eriti avatud ainsuse teise isiku kasutusest soome keeles ja teistes Euroopa keeltes. Artikkel keskendub neljale avatud viitesuhtega isikukonstruktsioonile – nullkonstruktsioon, netsessiivkonstruktsioon, ainsuse teise isiku ja imperatiivkonstruktsioon – ning nende vastastikusele mõjule ja varieerumisele piiriala karjala murrete suulises diskursuses. Artiklil on kolm eesmärki. Esimene ja peamine eesmärk on osutada, et eelmainitud avatud isikukonstruktsioonid moodustavad neli põhitüüpi. Teiseks, artikkel laiendab käimasolevat diskussiooni avatud viitesuhtest soome keeles, tutvustades ohustatud lähisugulaskeele, karjala keele isikusüsteemi. Kolmandaks tõstatab artikkel küsimuse, kas läänemeresoome keelte kontekstis on nullkonstruktsioon just soome keelele omane viis jätta viitesuhe avatuks ja täpsustamata.